Alternative learning technologies for developing capacity in animal breeding and genetics in middle and low income countries - Ojango, Julie M.K.; Rege, J.E.O.; Dror, Iddo; Kugonza, Donald R.; Chagunda, Mizeck G.G.; Mrode, Raphael A.; Philipsson, J.; Okeyo Mwai, Ally (2018)
In today’s world where scientific progress and development of new knowledge is increasing rapidly, middle and low income countries must be able to train and retain versatile researchers in the field of animal breeding and genetics able to analyze, adapt and use technologies, and possess strong social skills. A modernized blended learning approach with flexible organizational structures that allow the integration of face to face with virtual learning environments using various e-learning technologies needs to be adopted. However, electronic learning tools addressing situations and needs for animal genetic resource management in middle and low income countries are few, and several challenges hinder wide adoption of e-learning. This paper presents some experiences with e-learning tools in middle and low income countries, outlines opportunities for enhanced adoption of e-learning and identifies some gaps and questions that still need to be addressed to facilitate e-learning.